Analisis Semiotik pada Antologi Puisi Memeluk Ramadhan Bersimbah Wabah Karya Jumrah dkk serta Pemanfaatannya sebagai Bahan Pembelajaran Apresiasi Sastra di SMA - Mursadi, Mursadi (Universitas Mathla'ul Anwar Banten, 2023)
This research aims to describe the meaning contained in the poetry anthology Memeluk Ramadhan Bersimbah Plabah by Jumrah et al. Describe the signs, indices and symbols contained in the poetry anthology Memukuk Ramadhan Bersimbah Plabah by Jumrah et al. Utilizing the results of a semiotic study of the poetry anthology Embrace Ramadhan Bersimbah Plabah by Jumrah et al as learning material for literary appreciation in high school. This research is qualitative descriptive research, namely collecting, analyzing, using content analysis techniques. The form of description studied can be described as follows: Literary works are the result of human creativity which aims to express oneself, one of which is poetry. Poetry is an imaginative literary work resulting from the poet's expressions and feelings using beautiful (aesthetic) language. What must be considered is the reality of life in it, such as social reality and religious reality. The social reality contained in this collection of poems is that it describes or tells about unusual conditions in a country since the emergence of Covid-19, maintaining distance and reducing direct contact between humans must be done to prevent the transmission of Covid-19. Meanwhile, the religious reality contained in this poem is, always having a good opinion of Allah for everything that has been given to all His creatures, be it the blessings of faith and the blessings of Islam, as well as the blessings of health and sustenance that can be felt. Apart from that, gratitude for the presence of Ramadan will be a field of reward and erasure of sins and mistakes that have been made, as well as love for Allah who always strengthens them in facing all the tests they have to face. This research can be used as a use of teaching materials for students, namely class.